Analisis Penerapan Sistem Informasi Manajemen pada Instansi Pemerintah Daerah - Arya Agiltriawan; Muhammad Ilham; Isa Faqihuddin Hanif (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The implementation of management information systems is a crucial instrument for improving the effectiveness of performance and service quality in local government agencies. The digital transformation driven by national policy requires local governments to manage data and information in an integrated, accurate, and timely manner. However, in practice, the implementation of management information systems still faces various obstacles, both in terms of human resources, technological infrastructure, and organizational policy support. This study aims to analyze the implementation of management information systems in local government agencies and identify the supporting and inhibiting factors that influence it. The research method used is a qualitative approach through a literature review of national journals and relevant scientific papers published between 2021 and 2025. Data were analyzed descriptively and analytically to obtain a comprehensive picture of the implementation patterns of management information systems in local government. The analysis results indicate that management information systems contribute positively to improving the effectiveness of organizational performance and the quality of public services when supported by competent personnel, available infrastructure, and leadership commitment. Conversely, weak coordination, limited human resources, and resistance to change are the main factors hindering implementation. This research is expected to serve as evaluation material and a reference for local governments in optimizing the implementation of management information systems on a sustainable basis.